The Urgence Of Islamic Counseling In Overcoming Violations Of Student Disclaimers In Nurul Falah Islamic Boarding School Labuhan Batu Selatan Regency - Desrayanti Sullama; Saiful Akhyar Lubis; Mohammad Al Farabi; M Fajri Syahroni Siregar (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
The violations that students in Islamic boarding schools often experience are a significant problem that educators need serious attention to. However, in reality, in Nurul Falah Islamic Boarding School, many students still violate the applied discipline. So that the researcher wanted to find out how to use the field in the Nurul Falah Islamic Boarding School and how to overcome the violations of the rules that had been implemented in the Nurul Falah Islamic Boarding School. This research method is qualitative with a phenomenological approach. Phenomenology The data collection techniques in this study were carried out in three ways: observation, interviews, and documentation.